Spontaneous ejaculation; caused by venlafaxine, reverted by mirtazapine - Camkurt, Mehmet (The European Research Journal, 2015)
Spontaneous ejaculation is a rare side effect of antidepressants. SSRIs, SNRIs, and reboxetine are reported to cause spontaneous ejaculation. Previous reports suggest to stop or change medication in the presence of this side effect, and less is known how to manage patients who want to continue the medication with this side effect. Mirtazapine is a noradrenergic and specific serotonergic antidepressant, mostly used for the treatment of depression. It is recommended as an add-on pharmacotherapy to relieve sexual side effects. Here, we demonstrate a case of spontaneous ejaculation, caused by venlafaxine, and reverted by mirtazapine.